Proposing an integrated LCA-SCM model to evaluate the sustainability of customisation strategies. Issue 7 (3rd July 2017) - Fornasiero, Rosanna; Brondi, Carlo; Collatina, Davide
Abstract : The increasing level of customisation within manufacturing industry introduces a new degree of complexity in assessing the environmental impact on the product chain. In particular, when such assessments are devoted to complex effects, traditional methodologies require new developments. The aim of the present article is to propose a new assessment method combing life-cycle assessment (LCA) with discrete simulation to evaluate the sustainability of a company aiming to integrate different customisation policies in a networked context. In particular, a modular LCA can assess the environmental impact of a supply chain (SC) with different configurations. Then, based on different supply chain management (SCM) strategies, simulation is run creating scenarios by introducing variation of performance drivers such lead time to the customer, quality in terms of scraps and level of sustainability of the suppliers to support comparison of different kind of customisation. The preliminary results of the LCA-SCM model applied to the customisation case in the fashion sector highlights as specific decisional areas under the control of supply managers (e.g. supplier selection and manufacturing defects) can significantly affect the environmental impact of the whole SC.